The in vivo digestibility study of banana flour with high content of resistant starch at different ripening stages. Issue 12 (27th November 2020) - Yang, Jie; Bi, Yu; Liang, Shangyun; Gu, Zhengbiao; Cheng, Li; Li, Caiming; Li, Zhaofeng; Zhang, Yayuan; Hong, Yan
Abstract : Resistant starch, a functional food ingredient, can improve the nutritional value of food products. Abstract : Resistant starch, a functional food ingredient, can improve the nutritional value of food products. In this study, the in vitro digestibility of starch from banana flour at four ripening stages was evaluated. The result showed that the resistant starch content of banana flour at ripening stage 1 was up to 81%. Furthermore, to explore the effect of resistant starch in the body, the in vivo digestibility of banana flour was investigated. The intake of banana flour at ripening stage 1 resulted in a nearly 70% decrease in the homeostasis model assessment of insulin resistance value, compared to that of the model group. By contrast, the genes related to glucokinase were upregulated by 66%, and the expression level of the insulin receptor gene was increased by more than 1.5 times that of the model group. Thus, natural banana flour has potential for controlling type 2 diabetes mellitus.